2020
DOI: 10.1007/s11340-019-00566-4
|View full text |Cite
|
Sign up to set email alerts
|

Towards Criteria Characterizing the Metrological Performance of Full-field Measurement Techniques

Abstract: Users of full-field measurement methods like Digital Image Correlation (DIC) often aim to perform measurements with the best trade-off between spatial resolution, bias and measurement resolution. Whenever two full-field methods are compared, it is essential that these criteria are taken into consideration. Recently a metrological efficiency indicator for full-field measurements has been proposed and discussed. This indicator combines measurement resolution and spatial resolution. It has been shown to be invari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 63 publications
(107 reference statements)
0
29
0
Order By: Relevance
“…This curve can be considered as an intrinsic signature of a given technique when applied to a pair of reference and deformed images. In addition, if, as expected, the product σ u × d is really constant [18], considering a logarithmic scale for both quantities, as in [34], should lead to a straight line of slope -1 in the σ u -d plane. This enables us to easily visually observe whether this property (the fact that σ u × d is constant) is satisfied or not.…”
Section: Displacement Resolution As a Function Of The Spatial Resolutmentioning
confidence: 61%
See 1 more Smart Citation
“…This curve can be considered as an intrinsic signature of a given technique when applied to a pair of reference and deformed images. In addition, if, as expected, the product σ u × d is really constant [18], considering a logarithmic scale for both quantities, as in [34], should lead to a straight line of slope -1 in the σ u -d plane. This enables us to easily visually observe whether this property (the fact that σ u × d is constant) is satisfied or not.…”
Section: Displacement Resolution As a Function Of The Spatial Resolutmentioning
confidence: 61%
“…Inspired from recent studies on the metrological performance of various full-field measurement techniques [18,34], the procedure employed here consists in fixing the bias λ to the same value for both techniques, and then in examining how the measurement resolution σ u evolves as the spatial resolution d progressively changes. This latter quantity increases with the subset size 2M + 1 (DIC), and with (LSA).…”
Section: Link Between Bias Spatial Resolution and Measurement Resolumentioning
confidence: 99%
“…Another interesting conclusion of this second step is that quadratic matching functions (instead of bilinear ones) and steps of one pixel between successive subsets should systematically be used, leading to lower values of C 3 . The superiority of the quadratic shape functions has been documented in previous works, [136,137] while step size has, regrettably, not been the focus of much attention in the past. It is worth noting that the orientation of the fibres in OAUIT has also been optimized with this type of approach in the particular case of wood, see Kretschmann et al [96] In the same spirit as in the preceding study, a refinement of the work presented in Wang et al [121] on orthotropic polymeric foams (and discussed in the preceding section) tested with an Arcan fixture was proposed in Wang et al [64] The experimental device is shown in Figure 10.…”
Section: Design By Full Identification Simulationmentioning
confidence: 97%
“…However this result does not take into account the spatial resolution of the different techniques. As suggested in [9], this quantity, denoted by d, can be estimated by considering the cross-section of the displacement field returned by a given technique along its horizontal line of symmetry, and by finding the period of the sinusoidal vertical displacement such that a bias λ equal to 10% is observed, see Section 3.1 and [26,9,37] for instance. Figure 16 shows σ u as a function of d for WGPA and various settings (fives possibilities for Z f , six values for k), along with the same quantity obtained with LSA performed with and without deconvolution.…”
Section: Quantitative Comparison Between the Metrological Performancementioning
confidence: 99%
“…This is the price to pay to obtain a measurement defined nearly pixelwise, without any influence of the actual displacement that occurs at the surrounding pixels. In recent studies on LSA and DIC [39,37], it is proposed to assess the compromise between spatial resolution and displacement resolution by considering the product between these two quantities. The reason is that this product has been demonstrated (respectively observed) to be constant for LSA (respectively for DIC) in [38] (respectively [39]).…”
Section: Quantitative Comparison Between the Metrological Performancementioning
confidence: 99%